Modelling a portable personal health record - Santos, João C. (2010)
Active and responsible involvement of patients in their own health is accepted as an important contribution towards an increased quality of health services in general. Management of Personal Health Information by the patient can play an important role in the improvement in quality of the information available to health care professionals and as a means of patient involvement. Electronic Health Records are a means of storing this kind of information but their management usually falls under the responsibility of an institution and not on the patient himself. A Personal Health Record under the direct control and management of the patient is the natural solution for the problem. When implemented in a storage hardware portable device, a PHR, allows for total mobility. Personal Health Information is very sensitive in nature so any implementation has to address security and privacy issues. With this in mind we propose a structure for a secure Patient Health Record stored in a USB pen device under the patient’s direct management and responsibility.